PENGARUH TRANSPARANSI, AKUNTABILITAS DAN PERAN PERANGKAT DESA TERHADAP PENGELOLAAN KEUANGAN DESA (STUDI DI KECAMATAN TINADA, KABUPATEN PAKPAK BHARAT SUMATERA UTARA) - Kristi Geovani Tumangger; Salman, Muhammad; Nasrul Kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the effect of transparency, accountability and the role of village officials on village financial management in Tinada sub-district, Pakpak Bharat district. The sample in this study amounted to 36 respondents. The data analysis method used multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The regression equation in this study is Y = 0.951 - 0.495X1 + 0.211X2 + 1.003X3. Transparency has a significant effect on the financial management of the study village in Tinada sub-district, Pakpak Bharat district, where the t-value sig is 0.000 <0.05. Accountability has a significant effect on the financial management of the study village in Tinada sub-district, Pakpak Bharat district, where the t-value sig is 0.035 <0.05. The role of village officials has a significant effect on the financial management of the study village in Tinada sub-district, Pakpak Bharat district, where the t-value sig is 0.000 <0.05. Transparency, accountability, and the role of village officials simultaneously significantly influenced the financial management of the study village in Tinada sub-district, Pakpak Bharat Regency, with an F-value of 0.000 <0.05. The coefficient of determination test revealed that transparency, accountability, and the role of village officials influenced the financial management of the study village in Tinada sub-district, Pakpak Bharat Regency by 89.2%, while the remaining 10.8% was influenced by factors outside the research model. Keywords: Transparency, Accountability, Role of Village Officials, Village Financial Management